2021
DOI: 10.3390/ijms22031311
|View full text |Cite
|
Sign up to set email alerts
|

ELOVL5 Participates in Embryonic Lipid Determination of Cellular Membranes and Cytoplasmic Droplets

Abstract: Embryonic lipids are crucial for the formation of cellular membranes and dynamically participate in metabolic pathways. Cells can synthesize simple fatty acids, and the elongation of fatty acids facilitates the formation of complex lipids. The aim of this work was to investigate the involvement of the elongation of very long chain fatty acid enzyme 5 (ELOVL5) in embryonic development and lipid determination. Bovine embryos were produced in vitro using a standard protocol and randomly divided to receive one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Another study showed an increase in cytoplasmic lipid droplet deposition after transient gene expression knockdown of ELOVL5. Interestingly, no apparent deleterious effect on embryonic development and blastocyst cell number was observed, but a reduction in the expression of specific lipid genes was observed [82], demonstrating that further studies need to be conducted to clarify how altered lipid metabolism does not interfere with embryo quality.…”
Section: Embryosmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study showed an increase in cytoplasmic lipid droplet deposition after transient gene expression knockdown of ELOVL5. Interestingly, no apparent deleterious effect on embryonic development and blastocyst cell number was observed, but a reduction in the expression of specific lipid genes was observed [82], demonstrating that further studies need to be conducted to clarify how altered lipid metabolism does not interfere with embryo quality.…”
Section: Embryosmentioning
confidence: 97%
“…ACSL3 is related to the formation of LD in embryos. Similarly, elongation of very-long-chain fatty acids (ELOVL) is associated with the embryonic membrane phospholipid composition [65], and ELOVL5 modulates intracytoplasmic LD [82].…”
Section: Embryosmentioning
confidence: 99%
“…The ELOVL5 plays an important role in the determination of embryonic lipid droplet content. Blockage of ELOVL5 translation revealed a clear effect on the expression of particular lipids and promoted increased deposition of cytoplasmic lipid droplet (Lanzarini et al, 2021). A previous study concluded that overexpression of ELOVL5 gene at the morula stage preceded an increased abundance of a series of lipids at the blastocyst stage (Sudano et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Obesity and diabetes are independently associated with an altered female reproductive function [ 13 , 45 , 46 ]. Interestingly, a recent study reported that ELOVL5 is involved in embryonic development and lipid metabolism [ 47 ]. KLF2 is expressed in endothelial cells and inhibited by the inflammatory cytokine interleukin-1, hence, implicated as a novel regulator response to proinflammatory stimuli [ 48 ].…”
Section: Discussionmentioning
confidence: 99%